Association Between Bladder Management Strategies and Symptomatic Urinary Tract Infections in Patients with Chronic Spinal Cord Injury: Lessons from a 5-Year Longitudinal Cohort - Yu-Hui Huang; Chieh-Jui Chen; Yun-Sheng Chen; Kai-Siang Chen; Sung-Lang Chen (Journal of Clinical Medicine, 2026)
Background: Urinary tract infections (UTIs) are a leading cause of morbidity in patients with chronic spinal cord injury (SCI). This study examined the incidence of first and recurrent symptomatic UTIs in patients with chronic SCI and explored clinical factors associated with infection risk, with particular attention to bladder management methods and structural urinary tract abnormalities. Methods: We conducted a longitudinal observational study including 297 patients with chronic SCI (≥5 years post-injury; 215 males, 82 females with a mean age of 49.1 ± 13.8 years). Participants underwent regular evaluations, including kidney ultrasounds, videourodynamic studies (VUDS), and effective renal plasma flow (ERPF) measurements. Symptomatic UTIs were strictly defined using clinical–microbiological criteria to exclude asymptomatic bacteriuria (ASB). Clinical outcomes were evaluated over a minimum 5-year follow-up period. Results: Average annual symptomatic UTI rates were 0.31 ± 0.37 (major), 0.46 ± 0.47 (minor), and 0.77 ± 0.64 (total) episodes per patient-year. Bladder management method significantly influenced UTI rates (p < 0.001), with the highest rates observed in patients with indwelling urethral catheters (IUC) (1.19 ± 0.71), followed by suprapubic cystostomy (SPC) (0.91 ± 0.54), clean intermittent catheterization (CIC; 0.59 ± 0.47), and reflex voiding (0.31 ± 0.36). Recurrence (≥2 episodes) occurred in 23.9% of patients with indwelling catheters, 26.9% with suprapubic cystostomy, 13.0% with CIC, and 7.5% with reflex voiding. Patients with indwelling urethral catheters had higher total UTI rates and a higher recurrence rate than those with suprapubic cystostomy (1.19 vs. 0.91 episodes per patient-year; recurrence 38.8% vs. 26.9%). Hydronephrosis (Adjusted OR = 4.78, 95% CI: 2.45–9.32, and p < 0.001), bladder wall trabeculation (Adjusted OR = 3.65, 95% CI: 1.92–6.94, and p < 0.001), and indwelling catheter use (IUC + SPC) (Adjusted OR = 3.41, 95% CI: 1.85–6.29, and p < 0.001) were independently associated with increased UTI risk. Conclusions: Indwelling catheter use and specific structural upper and lower urinary tract abnormalities were independently associated with an increased risk of symptomatic UTIs in chronic SCI. Prioritizing CIC, routine monitoring with imaging and urodynamics, and implementing targeted preventive strategies may help reduce infection burden and preserve renal function.